Indigenous communities' perceptions reveal threats and management options of wild edible plants in semiarid lands of northwestern Kenya - Oluoch, Wyclife Agumba; Whitney, Cory W.; Termote, Céline; Borgemeister, Christian; Schmitt, Christine B. (Springer, 2023)
Background: Understanding how local communities perceive threats and management options of wild edible plants (WEPs) is essential in developing their conservation strategies and action plans. Due to their multiple use values, including nutrition, medicinal, construction, and cultural as well as biotic and abiotic pressures, WEPs are exposed to overexploitation, especially within arid and semiarid lands, and hence the need to manage and conserve them. We demonstrate how an understanding of indigenous communities’ perceptions could be achieved through an integrated participatory approach involving focus group discussions (FGDs) and feld plot surveys. Methods: We conducted three FGDs between October 2020 and April 2021 within three community units in northwestern Kenya with diferent socioeconomic and environmental characteristics. We subsequently surveyed 240 feld plots of size 1 ha each to assess threats facing WEPs within a 5 km bufer radius in every study community. We compared ranks of threats and management options across community units. Results: Rankings of threats and management options difered across the three study communities. We obtained strong positive linear relationships between feld and FGD rankings of threats facing WEPs. Climate change, overstocking, overharvesting, and invasive species were the highest-ranked threats. Mitigation of climate change, local knowledge preservation, selection, propagation, processing, and marketing of WEPs ranked high among possible management options irrespective of the socioeconomic and environmental characteristics of the community unit. Conclusions: Our approach emphasizes the relevance of leveraging indigenous communities’ perceptions and conducting feld plot surveys to assess threats and management options for WEPs. Evaluating the efectiveness and cost–beneft implications of implementing the highly ranked management options could help determine potentially suitable habitats of the WEPs for conservation and management purposes, especially for priority WEPs.